Upaya Meningkatkan Pemahaman Siswa dalam Pembelajaran Matematika melalui Penerapan Pendekatan Konstruktivisme di Kelas VIII-G SMP Negeri 12 Mataram - Asyiah, Siti (ANWARUL, 2023)
The purpose of this study was to find out: Students' understanding of learning Mathematics before applying the constructivism approach in class VIII.G of SMP Negeri 12 Mataram in the academic year 2022/2023; The student learning process in learning Mathematics uses a constructivism approach in each class cycle VIII.G SMP Negeri 12 Mataram for the 2022/2023 academic year; Increasing students' understanding of learning Mathematics through the application of a constructivism approach in each class cycle VIII.G of SMP Negeri 12 Mataram for the 2022/2023 academic year. This research is a Classroom Action Research (CAR), using two cycles through the planning, action, observation, and reflection stages. As subjects in this study were class VIII.G students for the 2022/2023 academic year with a total of 32 students, consisting of 17 male students and 15 female students. The results of the study were obtained from 32 students who took the class average score test before the action 72.09 or 59.38% classical completeness, to 74.69 or 74.69% classical completeness in cycle I, increased to an average of 78.19 or 96.88% in cycle II. From cycle I to cycle II and has shown the application of the constructivism approach can improve understanding and learning outcomes of Class VIII.G students of SMP Negeri 12 Mataram.